THE MORTGAGE LENDING MARKET IN THE CONDITIONS OF WAR AS AN ELEMENT OF THE ECONOMIC SECURITY OF THE BANKING SYSTEM - Kokhan , I. V.; Solodzhuk , T. V.; Krykhovetska , Z. M. (The actual problems of regional economy development, 2024)
Effective functioning of the banking system in terms of its credit component is the basis of the development of the country's economy, especially during the recovery period. An important element of the formation of long-term financial resources is the mortgage lending mechanism, which contributes to the additional increase of bank assets and solves the social problem of providing the population with housing. The socio-economic situation in the state often shows the current state of the real estate market. Russia's war against Ukraine caused the destruction of many real estate objects, led to a large number of internally displaced persons from the territories where there are active hostilities, which caused a significant need for residential objects for the specified categories of persons, and also significantly increased the need for renting of real estate in regions that are far away from active combat zones. In general, mortgage lending is a catalyst for the economic growth of the economy in the state, as thanks to it, investment in the real sector of the economy is implemented, and there is a steady increase in income in related types of economic activity. The mechanism of action of mortgage lending includes not only the financial component of the stability of banking institutions, but also affects the socio-economic, political, macroeconomic sphere of the life of society and the state, which forms a significant share of the state's assets. The article notes the state of mortgage lending in Ukraine in modern conditions, particularly in the context of economic instability and the introduction of martial law. The main areas of regulation, problems in the mortgage market and their impact on the stability of the banking system and socio-economic development in the state are indicated. In the context of these changes, the functioning of the state program "eOsel" as a practical tool for increasing mortgage lending and guaranteeing living conditions for citizens in the conditions of military operations is being investigated. The structure and dynamics of providing mortgage loans, in particular under the "eOselya" program, are analyzed, as well as the impact of these processes on the regional distribution of the market. Thus, directions of development and improvement of the mechanisms of the mortgage lending system in Ukraine have been formed, from the standpoint of economic security of banking activity, it meets the current requirements of today.